The DCMU Herbicide Shapes T-cell Functions By Modulating Micro-RNA Expression Profiles - Autin, Pierre; Deshayes, Sophie; Lea, Juliette; Boisgerault, Nicolas; Dupré, Emilie; Labarrière, Nathalie; Leguevel, Rémy; Fonteneau, Jean-François; Blanquart, Christophe; Fradin, Delphine (Frontiers in Immunology, 2022)
DCMU (N-(3,4-dichlorophenyl)-N-dimethylurea) or diuron, is a widely used herbicide, which can cause adverse effects on human, especially on immune cells due to their intrinsic properties and wide distribution. These cells are important, of course, for fighting against virus or bacteria but also, against neoplastic cell development. We developed an approach that combines functional studies, miRNA and RNA sequencing data to evaluate the effects of DCMU on the human immune response against cancer, particularly the one carried out by CD8+ T cells. We found that DCMU modulates the expression of miRNA in a dose dependent manner, leading to a specific pattern of gene expression and consequently to a diminished cytokine and granzyme B secretions. Using mimics or anti-miRs, we identified several miRNA, such as hsa-miR-3135b and hsa-miR-21-5p, that regulate these secretions. All these changes reduce the CD8+ T cells’ cytotoxic activity directed against cancer cells, in vitro and in vivo in a zebrafish model. To conclude, our study suggests that DCMU reduces T cell abilities, participating thus to the establishment of an environment conducive to cancer development.